Sweetgum: An ancient source of beneficial compounds with modern benefits - Lingbeck, Jody M.; O’Bryan, Corliss A.; Martin, Elizabeth M.; Adams, Joshua P.; Crandall, Philip G. (Pharmacognosy Reviews)
Sweetgum trees are large, deciduous trees found in Asia and North America. Sweetgum trees are important resources for medicinal and other beneficial compounds. Many of the medicinal properties of sweetgum are derived from the resinous sap that exudes when the outer bark of the tree has been damaged. The sap, known as storax, has been used for centuries to treat common ailments such as skin problems, coughs, and ulcers. More recently, storax has proven to be a strong antimicrobial agent even against multidrug resistant bacteria such as methicillin‑resistant Staphylococcus aureus. In addition to the sap, the leaves, bark, and seeds of sweetgum also possess beneficial compounds such as shikimic acid, a precursor to the production of oseltamivir phosphate, the active ingredient in Tamiflu®–an antiviral drug effective against several influenza viruses. Other extracts derived from sweetgum trees have shown potential as antioxidants, anti‑inflammatory agents, and chemopreventive agents. The compounds found in the extracts derived from sweetgum sap suppress hypertension in mice. Extracts from sweetgum seeds have anticonvulsant effects, which may make them suitable in the treatment of epilepsy. In addition to the potential medicinal uses of sweetgum extracts, the extracts of the sap possess antifungal activity against various phytopathogenic fungi and have been effective treatments for reducing nematodes and the yellow mosquito, Aedes aegypti, populations thus highlighting the potential of these extracts as environment‑friendly pesticides and antifungal agents. The list of value‑added products derived from sweetgum trees can be increased by continued research of this abundantly occurring tree.
Keywords: Anti‑inflammatory; antimicrobial; antioxidant; Liquidambar; storax; sweetgum